Biobanking in Israel 2016–17; expressed perceptions versus real life enrollment - Koren, Gideon (BMC Med Ethics, 2017)
BACKGROUND: As part of the preparations to establish a population-based biobank in a large Israeli health organization, we aimed to investigate through focus groups the knowledge, perceptions and attitudes of insured Israelis, toward biobanking, and then, after input from focus groups’ participants, to empirically assess the impact of a revised recruitment process on recruitment rates. METHODS: 1. Six Focus group discussions were conducted (n = 10 per group) with individuals who had routine blood laboratory tests taken in the last 2 years. 2. After addressing the issues raised in the focus groups and revising the recruitment process, individuals undergoing routine blood tests in phlebotomy clinics (N = 10,262) were invited to participate in the future biobank. RESULTS: At the outset of the focus groups there was an overall positive response to the prospect of a population-based biobank. Concerns revolved around infringement on privacy, fears of the “big brother”(e.g. insurance companies), and anxiety about inequality. Reaction to the language of the informed consent document revolved around concerns over ability to maintain anonymity, to withdraw consent, involvement of commercial entities, and the general tenor of the informed consent, which was perceived as legalistic and unilateral. In general, the longer participants were exposed to discussion about the biobank, the less likely they were to consent to sign in. Overall, only 20% (12) of the 60 participants stated they would agree to sign in by the end of the 2 hour group session. The feedback obtained from the focus groups was used in the second stage (“real life”) of the study. A team of recruiters received extensive training to enable fruitful discussion and a detailed explanation to questions and concerns raised during the recruitment process. During the second stage of the study, after revising the consent form and training recruiters, a 53% consent rate was observed among 10,262 participants, more than 4 fold higher than estimated at the focus group stage. CONCLUSIONS: The qualitative focus group research helped identify important perceptions and concerns, which were subsequently addressed in the revised consent form and in the discussion the recruiters had with potential biobank donors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12910-017-0223-8) contains supplementary material, which is available to authorized users.